Propionate metabolism in a human pathogenic fungus: proteomic and biochemical analyses - Luiz Paulo Araújo Santos; Leandro do Prado Assunção; Patrícia de Souza Lima; Gabriel Brum Tristão; Matthias Brock; Clayton Luiz Borges; Mirelle Garcia Silva-Bailão; Célia Maria de Almeida Soares; Alexandre Melo Bailão (IMA Fungus, 2020)
Abstract Fungi of the complex Paracoccidioides spp. are thermodimorphic organisms that cause Paracoccidioidomycosis, one of the most prevalent mycoses in Latin America. These fungi present metabolic mechanisms that contribute to the fungal survival in host tissues. Paracoccidioides lutzii activates glycolysis and fermentation while inactivates aerobic metabolism in iron deprivation, a condition found during infection. In lungs Paracoccidioides brasiliensis face a glucose poor environment and relies on the beta-oxidation to support energy requirement. During mycelium to yeast transition P. lutzii cells up-regulate transcripts related to lipid metabolism and cell wall remodeling in order to cope with the host body temperature. Paracoccidioides spp. cells also induce transcripts/enzymes of the methylcitrate cycle (MCC), a pathway responsible for propionyl-CoA metabolism. Propionyl-CoA is a toxic compound formed during the degradation of odd-chain fatty acids, branched chain amino acids and cholesterol. Therefore, fungi require a functional MCC for full virulence and the ability to metabolize propionyl-CoA is related to the virulence traits in Paracoccidioides spp. On this way we sought to characterize the propionate metabolism in Paracoccidioides spp. The data collected showed that P. lutzii grows in propionate and activates the MCC by accumulating transcripts and proteins of methylcitrate synthase (MCS), methylcitrate dehydratase (MCD) and methylisocitrate lyase (MCL). Biochemical characterization of MCS showed that the enzyme is regulated by phosphorylation, an event not yet described. Proteomic analyses further indicate that P. lutzii yeast cells degrades lipids and amino acids to support the carbon requirement for propionate metabolism. The induction of a putative propionate kinase suggests that fungal cells use propionyl-phosphate as an intermediate in the production of toxic propionyl-CoA. Concluding, the metabolism of propionate in P. lutzii is under regulation at transcriptional and phosphorylation levels and that survival on this carbon source requires additional mechanisms other than activation of MCC.